Physiological and Sprint Kinetics Associated With the Yo-Yo Intermittent Recovery Test Level 1 Performances in Soccer Players - Kramer, M.; Sparks, M.; Coetzee, B. (International Journal of Sports Physiology and Performance, 2022)
Background: The Yo-Yo Intermittent Recovery Test Level 1 (YYIR1) is often utilized to indirectly assess the cardiorespiratory fitness of team-sport athletes due to its proposed association with match-play high-speed running performance and predicted maximal oxygen uptake. No previous research has investigated the relationships between YYIR1 performances, actual oxygen uptake recorded during the YYIR1, and true all-out sprint kinetics (eg, maximal sprint speed, maximal force capacity, and maximal power output), which therefore served as the primary objective of this study. Objectives: To assess the true physiological kinetics (VO2 and heart-rate responses) during the YYIR1 and to evaluate the correlations between the physiological kinetics, sprint kinetics, and YYIR1 performance parameters. Methods: A total of 23 amateur male soccer players were recruited for the study (age 22.52 [2.86] y; height 1.75 [0.06] m; body mass 65.61 [8.43] kg). Each participant completed a YYIR1 and 2 all-out sprint tests. Results: Significant differences were observed between actual and predicted maximal oxygen-uptake values (Mdiff = 17.57 mL·kg-1·min-1, P < .001, r = .63). Shuttle distances showed statistically significant correlations with maximal sprint speed (r = .42, P = .044) and theoretic maximal speed (r = .44, P = .035). However, no other correlations with sprint kinetic parameters (eg, maximal force or power output) were observed. Conclusion: Practitioners should carefully consider the outcomes and utilities of the parameters derived from the YYIR1. The estimations of maximal oxygen uptake from shuttle performances as a proxy for cardiorespiratory fitness are not adequate. However, shuttle distances appear to be positively associated with all-out sprinting capacities.